Pengaruh Motivasi terhadap Kinerja Pegawai di Kantor Kecamatan Cibadak Kabupaten Lebak Provinsi Banten - Permana, Deni; Setiadin (JURNAL ILMIAH RESEARCH AND DEVELOPMENT STUDENT, 2023)
Employee performance appraisal is an important matter of an organization or institution, especially public service organizations. Many factors affect employee performance, both internal and external factors. One of the internal factors is motivation. This research was conducted at the Cibadak District Office, Lebak Regency, Banten Province, which aims to determine the effect of motivation on employee performance in the Cibadak District Office, Lebak Regency, Banten Province. The sampling technique uses saturated sampling, namely as many as 35 people using a questionnaire. Data analysis using correlation and regression techniques. From the results of the research conducted, it shows that employee motivation has a significant effect on employee performance in the Cibadak District Office, Lebak Regency, Banten Province. This is evidenced by the value of the hypothesis test tcount > ttable = 14.408 > 1.689 and from the significance value α(0.00) <0.05.